Experimental investigation of textile dyeing wastewater treatment using aluminium in electro coagulation process and Fenton's reagent in advanced oxidation process. (2021) - Kothai, A.; Sathishkumar, C.; Muthupriya, R.; sankar, K. Siva; Dharchana, R.
Abstract: To investigate the effectiveness of advanced treatment methods such as Electro coagulation (EC) and advanced oxidation process (AOP) in order to minimize the Colour, concentration of chemical oxygen demand and biochemical oxygen demand for the samples collected from textile dyeing waste water. Experiments carried out at lab scale model. The EC process was conducted by varying voltages such as 8 V, 10 V, 12 V, 14 V, 16 V and for duration of 60 mins each. AOP involves oxidation process in the wastewater using Fenton's reagent (Fe 2+ /H2 O2 ). The experiment was conducted at three different dosages such as 3 g + 30 ml, 4 g + 40 ml and 5 g + 50 ml of Fe 2+ and H2 O2 . From the results obtained, the removal efficiency was determined by comparing the important parameters such as COD, BOD and Colour of treated water as well as untreated waste water. The obtained results from the treatments were in accordance with the standards given by Central Pollution Control Board (CPCB) of India for textile wastewater discharge.